If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + -49 = 47 Reorder the terms: -49 + 3g = 47 Solving -49 + 3g = 47 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '49' to each side of the equation. -49 + 49 + 3g = 47 + 49 Combine like terms: -49 + 49 = 0 0 + 3g = 47 + 49 3g = 47 + 49 Combine like terms: 47 + 49 = 96 3g = 96 Divide each side by '3'. g = 32 Simplifying g = 32
| 5m+7n=35 | | x^4-11x^2+28=x | | 6-y=2y | | 6n+10=3 | | 9(1+9k)= | | 0.14=0.0001 | | u^2+250=0 | | M^2+3M= | | -15/-5=3 | | 0.13=0.001 | | x-7.5=-2x | | -6x=4y+1 | | 14+3n=8n-3+(n-4) | | 8(4-M)=8+4M | | 2l=5l-60 | | 88.1-2.3=72.46 | | 0.12=0.01 | | 200000+(60)=300000+(25) | | 3=3+5k-5 | | 6x+5=2x-3 | | 12+(x+9)=7 | | 2l=60-5l | | -42p-4p=-12 | | -15.3=7.5+55.2 | | 35(100000)= | | 0=-4.9t^2+19.6t+58.8 | | 2(l)=60-5(l) | | h=-4.9t^2+19.6t+58.8 | | -2x+7y=-9 | | 10x+5=26 | | =3x+x+x+5+2x+3+x+5 | | 4(a-5)+2=a+3 |